Obstacles to implementation of solvency li regime in nonlife insurance companies in Bosnia and Herzegovina - Safet Kozarevic; Zeljko Sain; Adela Hodzic (UTMS Journal of Economics, 2014)
Aimed at protection of the market and consumers, the control of solvency is very important for insurer's business activities. Regarding the fact that insurer's insolvency causes a chain of problems, the state regulation is needed that forces insurers to keep their solvency at the necessary level. Insurance companies in the European Union work on the implementation of a new regulatory framework defined by the Solvency II Directive, which demands a better risk management as well as a better connection of capital and risk profile, increased transparency, and higher flexibility of insurance companies' business. In the period to come, this would present a huge challenge for the authorities in Bosnia and Herzegovina (BiH) as well, which would need to prepare their resources for the introduction of the Solvency II concept. For this purpose, the analysis of the current condition of the insurance market in BiH was made. By using the primary research and applying the survey as a questioning technique, the attitudes were gathered on the current conditions and possibilities for the implementation of the Solvency II Directive into the business activities of insurance companies in BiH.
Keywords: G22; G28; 330; nonlife insurers; Solvency II; capital adequacy; solvency margin